PENGARUH PERENCANAAN ANGGARAN DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP EFEKTIVITAS KINERJA PEMERINTAH DAERAH KABUPATEN GRESIK - Nina Anggraini Anandah; Muhammad Aufa (Universitas Muhammadiyah Metro, 2023)
This research aims to examine the effect of budget planning and the quality of human resources on the effectiveness of the performance of the local government of Kabupaten Gresik.The sample in this study were regional apparatus organizations in Kabupaten Gresik, based on the purposive sampling method obtained 24 OPD. In this study the data were processed using SPSS with multiple linear regression. The method of testing the hypothesis uses a significance level of 5%. The result showed the budget planning has a significant effect on the effectiveness of government performance. While the quality of human resources has no significant effect on the effectiveness of government performance